Hemingway a film by Ken Burns and Lynn Novick - Ward, Geoffrey C. 1940- (PBS, 2021)
Examine the visionary work and turbulent life of one of the greatest and most influential American writers: Ernest Hemingway. Intimate and insightful, the series weaves together Hemingway's biography with excerpts from his work. The film penetrates the myth of Hemingway to reveal a deeply troubled and ultimately tragic figure
Container indicates Spanish SDH subtitles, disc menu does not (only regular Spanish subtitles)
Originally broadcast as a three-part PBS documentary series in 2021
"The man. The myth. The writer revealed"--Container
Widescreen (16x9)
Title from disc surface
Keywords: Hemingway, Ernest / 1899-1961; Authors, American / 20th century / Biography; Autores estadounidenses / Siglo XX / Biografía; Authors, American; 1900-1999; Video recordings for the hearing impaired; Television mini-series; Nonfiction television programs; Documentary television programs; Biographical television programs; Biographies; Film; DVD-Video